2015
DOI: 10.1590/2359-3997000000139
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary metastasis of lung neuroendocrine carcinoma: case report and literature review

Abstract: SUMMARYMetastasis to the pituitary gland is an unusual situation in clinical practice, but the frequency thereof is increasing due to the increased survival of cancer patients, and greater availability of imaging. In most cases, they are found between the sixth and seventh decades of life, as determined in image examination of patients with known malignant neoplasm, but, generally, asymptomatic with respect to pituitary involvement. The most common primary sites are breast in women and lung in men. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Within the lung malignancies with non-small histologies, LCNEC is cancer with a worse prognosis, even in early stages after complete resection. [ 10 ] Dresler et al demonstrated a 5-year survival for stage I LCNEC cases of 18%. In contrast, based on Iyoda et al's results, this disease encompasses a 5-year survival rate of 35.5% and a 5 year disease-free survival rate of 27.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Within the lung malignancies with non-small histologies, LCNEC is cancer with a worse prognosis, even in early stages after complete resection. [ 10 ] Dresler et al demonstrated a 5-year survival for stage I LCNEC cases of 18%. In contrast, based on Iyoda et al's results, this disease encompasses a 5-year survival rate of 35.5% and a 5 year disease-free survival rate of 27.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common origins of sellar metastases in women originate from the breast and lung in men. [ 15 , 18 , 30 ] Within neuroendocrine neoplasms, only a handful of reports have been previously published describing metastases to the sella. These studies were most recently reviewed by Goglia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Metastases to the region of the sella remain uncommon, representing approximately 1% of all sellar tumors. [ 30 ] However, with increased frequency of surveillance imaging of the central nervous system in tandem with prolonged overall survival of patients with a previously known diagnosis of cancer, metastasis must remain among the differential diagnosis for newly diagnosed lesions within the sellar region. While the various clinicopathologic characteristics pertaining to the presentation of patients with metastases to the sella continues to amount, including pituitary dysfunction, no studies have reported the underlying genetic alterations that may promote such spread.…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de anormalidades endocrinológicas asociadas con el carcinoma broncogénico resulta de una excesiva secreción de hormonas o sustancias similares a las hormonas como la secreción inadecuada de ADH o el síndrome de Cushing. El panhipopituitarismo es inusual y la sintomatología que se presenta con más frecuencia es la diabetes insípida y de forma infrecuente la afectación del lóbulo anterior hipofisiario (6), en el caso de la paciente se evidenció un hipotiroidismo central, hipogonadismo central, hipocortisolismo, diabetes insípida (confirmada por el test de desmopresina y medición de osmolaridad urinaria), además hiperprolactinemia por efecto compresivo metastásico, aunque se resalta que hay reportes de prolactinoma asociado (7). El clínico debe sospechar metástasis hipofisiaria con la siguiente triada clínica: diabetes insípida (polidipsia, poliuria y sed), oftalmoplejía y cefalea en un paciente mayor de 50 años, independientemente de una historia de malignidad (8-10), en ocasiones, la manifestación de convulsiones y cefalea puede sugerir compromiso hipofisiario (11).…”
Section: Discussionunclassified